The R136 star cluster hosts several stars whose individual masses greatly exceed the accepted 150 M-circle dot stellar mass limit - Crowther, P.A.; Schnurr, O.; Hirschi, R.; Yusof, N.; Parker, R.J.; Goodwin, S.P.; Abu Kassim, H. (Oxford University Press, 2010)
Spectroscopic analyses of hydrogen-rich WN 5-6 stars within the young star clusters NGC 3603 and R136 are presented, using archival Hubble Space Telescope and Very Large Telescope spectroscopy, and high spatial resolution near-IR photometry, including Multi-Conjugate Adaptive Optics Demonstrator (MAD) imaging of R136. We derive high stellar temperatures for the WN stars in NGC 3603 (T-* similar to 42 +/- 2 kK) and R136 (T-* similar to 53 +/- 3 kK) plus clumping-corrected mass-loss rates of 2-5 x 10(-5) M-circle dot yr(-1) which closely agree with theoretical predictions from Vink et al. These stars make a disproportionate contribution to the global ionizing and mechanical wind power budget of their host clusters. Indeed, R136a1 alone supplies similar to 7 per cent of the ionizing flux of the entire 30 Doradus region. Comparisons with stellar models calculated for the main-sequence evolution of 85-500 M-circle dot accounting for rotation suggest ages of similar to 1.5 Myr and initial masses in the range 105-170 M-circle dot for three systems in NGC 3603, plus 165-320 M-circle dot for four stars in R136. Our high stellar masses are supported by consistent spectroscopic and dynamical mass determinations for the components of NGC 3603A1. We consider the predicted X-ray luminosity of the R136 stars if they were close, colliding wind binaries. R136c is consistent with a colliding wind binary system. However, short period, colliding wind systems are excluded for R136a WN stars if mass ratios are of order unity. Widely separated systems would have been expected to harden owing to early dynamical encounters with other massive stars within such a high-density environment. From simulated star clusters, whose constituents are randomly sampled from the Kroupa initial mass function, both NGC 3603 and R136 are consistent with an tentative upper mass limit of similar to 300 M-circle dot. The Arches cluster is either too old to be used to diagnose the upper mass limit, exhibits a deficiency of very massive stars, or more likely stellar masses have been underestimated - initial masses for the most luminous stars in the Arches cluster approach 200 M-circle dot according to contemporary stellar and photometric results. The potential for stars greatly exceeding 150 M-circle dot within metal-poor galaxies suggests that such pair-instability supernovae could occur within the local universe, as has been claimed for SN 2007bi.